2024
DOI: 10.1021/acs.orglett.4c00010
|View full text |Cite
|
Sign up to set email alerts
|

Radical Hydro-Fluorosulfonylation of Propargylic Alcohols via Electron Donor–Acceptor Photoactivation

Yingyin Zhang,
Qingyuan Feng,
Yu Zheng
et al.

Abstract: A radical hydro-fluorosulfonylation of propargyl alcohols with FSO 2 Cl is presented based on the photoactivation of the electron donor−acceptor (EDA) complex. The reaction avoids the requirement for photocatalysts, bases, hydrogen donor reagents, any other additives, and harsh conditions, enabling the facile synthesis of various functionalized γ-hydroxy (E)alkenylsulfonyl fluorides. These multifunctional sulfonyl fluorides can be further diversified, providing access to various privileged molecules of biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…On the basis of the above studies and previous reports, , a plausible mechanism for this ring-opening fluorosulfonylation is proposed in Scheme D. To begin with, the interaction between methylenecycylobutanol 1 and FSO 2 Cl in diethyl ether produces EDA complex I .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…On the basis of the above studies and previous reports, , a plausible mechanism for this ring-opening fluorosulfonylation is proposed in Scheme D. To begin with, the interaction between methylenecycylobutanol 1 and FSO 2 Cl in diethyl ether produces EDA complex I .…”
mentioning
confidence: 75%
“…Recently, we have shown that strong electrophilic sulfuryl chlorofluoride (FSO 2 Cl) displays significantly different reactivity from alkyl or aryl sulfonyl chlorides . It can readily form EDA complexes with weak electron donors, propargyl alcohols, to trigger the FSO 2 radical formation . Inspired by the radical-mediated C–C bond cleavage of cyclobutanols, , we hypothesized that the FSO 2 radical would induce a similar transformation to offer a new strategy for the synthesis of multifunctional sulfonyl fluorides.…”
mentioning
confidence: 99%
“…We have recently shown that the fluorosulfonyl radical (FSO 2 •) can be generated via electron donor–acceptor (EDA) photoactivation . Building on these findings and drawing inspiration from radical fluorosulfonylation using sulfuryl chlorofluoride (FSO 2 Cl), we report a FSO 2 radical-mediated C–H cyclization of arenynes through visible light-activated EDA complexes for the synthesis of benzo-fused carbocycles and heterocycles (Scheme D).…”
mentioning
confidence: 94%
“…On the basis of the results presented above and related reports, , we proposed a plausible reaction mechanism (Scheme C). The reaction proceeds through the excitation of EDA complex I , forming the FSO 2 radical and radical cation II .…”
mentioning
confidence: 99%